P304 Predicting severity in Crohn's disease. (25th January 2019) - Gouveia, C; Gomes, C; Glória, L; Torres, J; Cravo, M
Abstract: Background: Stratification of patients with Crohn's disease (CD) according to the risk of developing complications is essential to delineate therapeutic approach. A recent score (Siegel et al ., Gut 2017) aims to assess disease severity, considering clinical and endoscopic activity, and complications during disease course, ranging from 0 to 100 values. Purpose: Evaluate the predictive capacity of this score at diagnosis (dx) for disease complications during the follow-up (surgery and hospitalisation). Methods: Retrospective study, including incident patients with CD at our hospital between January 2012 and July 2017. The score was calculated at dx and at the end of follow-up, and information about disease course was collected. Results: In total, 64 patients (32 women), with mean age at dx 33.4 ± 15.4 years. At dx 29 patients (45%) had L1 disease, 12 patients L2, 22 patients L3, and 1 patient L4. Forty-three patients (67%) had B1 phenotype, 7 patients B2, and 14 patients B3. At follow-up, 28 patients (44%) required surgery, 33 (52%) required hospitalisation, and 2 had phenotype progression. Median score at dx was 16 (4–50) and at follow-up was 9 (0–39). At dx score was higher in younger patients (22 A1 vs. 14 A3, p = 0.05), patients with penetrating phenotype (25 B3 vs. 11 B2, p = 0.005) and there was a tendency to a higher score in patients with upper GI disease (26 vs. 18, p = 0.07) and in those requiring surgery (21 vs. 18, p = 0.1). There was a positive correlation between score at dx and number of surgeries ( r = 0.29, p = 0.002) and hospitalisations ( r = 0.37, p = 0.018). There was a tendency for patients with a higher score at dx to have a shorter mean time to surgery ( p log-rank=0.07). At follow-up, there was a score decrease in 46 patients (72%), with 11 having a score of 0, an increase in 16 patients, and the score remained the same in 2 patients. Patients in whom the score decreased below median (<16) were more frequently patients without hospitalisations ( p = 0.03) or surgeries ( p = 0.008) at follow-up. There was no difference in score at follow-up regarding different therapies. Conclusions: The aforementioned severity score seems to be a promising instrument for stratification and prognosis of patients with CD, and its usefulness should be validated in prospective studies.